2022
DOI: 10.3390/ijms23179863
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Anti-Atopic Dermatitis Effects of α-Boswellic Acid on Tnf-α/Ifn-γ-Stimulated HaCat Cells and DNCB-Induced BALB/c Mice

Abstract: Boswellic acids, triterpenoids derived from the genus Boswellia (Burseraceae), are known for their anti-inflammatory and anti-tumor efficacy. Atopic dermatitis is a chronic, non-infectious inflammatory skin disease. However, the effects of α-boswellic acid on atopic dermatitis have not been studied. Therefore, in this study we examined the expression level of pro-inflammatory cytokines, histopathological analysis, and physiological data from BALB/c mice with atopic-like dermatitis induced by 2,4-dinitrochlorob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Many studies have shown that IFN-γ and TNF-α stimulate keratinocytes to induce signaling pathways involved in pro-inflammatory responses. Therefore, this model is often used as an in vitro test method for skin anti-inflammatory effectiveness [ 24 , 25 ]. It is shown in Figure 2 that once these pro-inflammatory cytokines (TNF-α and IFN-γ) are added, the formation of intracellular cytokine mRNA is significantly increased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that IFN-γ and TNF-α stimulate keratinocytes to induce signaling pathways involved in pro-inflammatory responses. Therefore, this model is often used as an in vitro test method for skin anti-inflammatory effectiveness [ 24 , 25 ]. It is shown in Figure 2 that once these pro-inflammatory cytokines (TNF-α and IFN-γ) are added, the formation of intracellular cytokine mRNA is significantly increased.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, these results show that its ability to resist atopic dermatitis is not inferior to that of components isolated from land plants. Moreover, their mechanism of action is very similar [ 24 , 25 , 51 ]. Future work will look to identify any unique mechanisms that are used by zoanthamine alkaloids to promote anti-inflammatory dermatitis effects.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the MAPK pathway, activated by EGF and EGFR signals, has been shown to control a wide range of physiological and pathological processes, including cell proliferation, gene expression, programmed cell death, and inflammation . Prior research has suggested that diminishing the expression of EGFR within the MAPK pathway can effectively alleviate the symptoms of AD in mice. , MAPKs, including ERK1/2 (MAPK3/1), JNK1/2/3, and p38 proteins (MAPK14), have been reported to be involved in AD. IL-1β1, IL-6, and TNF-α act as proinflammatory cytokine genes, which can be activated by MAPK signaling pathways . Generally, an important cause of AD is the dysregulated Th1 and Th2 response .…”
Section: Discussionmentioning
confidence: 99%
“… 39 , 40 MAPKs, including ERK1/2 (MAPK3/1), JNK1/2/3, and p38 proteins (MAPK14), have been reported to be involved in AD. 41 43 IL-1β1, IL-6, and TNF-α act as proinflammatory cytokine genes, which can be activated by MAPK signaling pathways. 44 Generally, an important cause of AD is the dysregulated Th1 and Th2 response.…”
Section: Discussionmentioning
confidence: 99%
“…The drugs that against AD included various topical corticosteroids (TCSs), tacrolimus and pyrrolimus, as well as antihistamines and immunosuppressants. 25 However, these are under a variety of adverse reactions when utilised for a long time or in large doses. Soaring medical costs reduced their clinical value although many effective biological agents have been used for treatment in AD in recent years.…”
Section: Discussionmentioning
confidence: 99%